Force majeure as grounds for exemption from contractual liability (Eurasian Research Bulletin, 2023)
The article deals with the definition of force majeure, force majeure as a basis for exemption from legal liability. The degree of influence on the conditions and possibilities of fulfilling the obligations of the parties under various trade agreements as a result of the introduction of a force majeure situation throughout the country is also considered. In this regard, businesses are interested in possible options for exemption from liability for improper performance of duties caused by force majeure. Taking this into account, the article analyzes the fact that answers the question of recognizing force majeure as exemption from liability, about the circumstances that should be recognized as force majeure and the reasons that contribute to exemption from liability for improper performance of obligations. In certain cases, force majeure is prescribed in the contracts as a reason for exemption from contractual liability, but many business entities do not specifically list in the contracts the cases that will be recognized as force majeure. The article compares different types of contracts, which contain clauses on force majeure.